MODELO MATEMÁTICO PARA ROTEAMENTO DE VEÍCULOS COM ARRUMAÇÃO DA CARGA EM TRÊS DIMENSÕES CONSIDERANDO RESTRIÇÃO DO PESO POR EIXO IMPOSTA POR LEI - Uliana, Bruna Curto (2022)
Road vehicles are designed to support a maximum axle weight limit. When the weight on an axle is above the limit value, the tires and the brake system wear out more quickly, there is a risk of suspension breakage, higher fuel consumption and consequently the vehicle's maintenance will have to be greater. Furthermore, there is also damage to national highways, since if there is excess weight on a single axle, the impact on the ground will be more harmful. In Brazil, there is CONTRAN Resolution n. 210, known as Lei da Balança, which sets weight limits on each vehicle axle. Thus, this dissertation proposes a mathematical model that elaborates the routes of the vehicles and their respective arrangement of the loads in the multiple compartments of the vehicles and, that considers the restrictions of weight per axle according to the current legislation. The proposed model was based on the Capacitated Vehicle Routing Problem with Three-dimensional Loading Constraints (3L-CVRP). Therefore, the arrangement of loads elaborated by the mathematical model must guarantee that the weight on the axles does not exceed that established in the legislation. The model was tested using the software CPLEX 12.20. In most test instances, vehicle routes were obtained with their respective three-dimensional cargo storage in multiple compartments considering the weight limit on each axle of the vehicle.